Antecedents and outcomes of employee-based brand equity - Bari, Muhammad Waseem, 1980-; Abrar, Muhammad, 1976-; Alaverdov, Emilia, 1978- (Advances in business strategy and competitive advantage., 2022)
"The purpose of this book is to enhance researchers and practitioners' understanding of how brand equity (employee perspective) could be fruitful in understanding and learning different theories and concepts with the interaction of different industries and cultures"--